(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
Acceleration of technical progress, increase in the assortment of chemical products, increase in labor productivity and quality of products from plasmas are to a certain extent related to acquisition and use of new types of polymer materials. With the development of air and space mechanics, the need for polymers with high atmospheric tolerance, heat, and long service life is increasing. Today, polyethylene terephthalate is used in the production of films, microorganism and mold resistant synthetic fibers, radio parts, and chemical equipment. This article describes the polycondensation process of polyethylene terephthalate in the solid phase.